The Influence of Information Technology Users, Employee Empowerment, and Work Culture on Employee Performance at the Ministry of Law and Human Rights Regional Office of Riau Islands - Pradanna Putra Tampi; Septa Diana Nabella; Dewi Permata Sari (Enrichment : Journal of Management, 2022)
This research examines the influence of Information Technology, Employee Empowerment, and Work Culture on Employee Performance at the Ministry of Law and Human Rights of the Riau Islands Regional Office. The sampling technique used by the researcher is the Simple Random Sampling Technique using the formula from Slovin. The data collection technique in this study used a questionnaire that was given directly to the respondents. The data analysis method used by the researcher is a descriptive quantitative analysis using Multiple Linear Regression, Classical Assumption Tests, t-tests, and F-test and the coefficient of determination. The results of this study are the three independent variables namely Information Technology, Employee Empowerment, and Work Culture partially and simultaneously have a positive and significant effect on employee performance at the Ministry of Law and Human Rights Regional Office of Riau Islands